Pengaruh Live streaming, Gratis Ongkir, dan Bonus pack Terhadap Keputusan Pembelian Produk Fashion di TikTok Shop pada Generasi Z - Samuel T.A; Irwan Christanto Edy (Jurnal Minfo Polgan, 2026)
The purpose of this study was to examine the influence of live streaming, free shipping, and bonus packs on fashion product purchasing decisions on TikTok Shop among Generation Z students of the Bukit Pengharapan Christian Institute of Technology and Business. This study used a quantitative approach with a causal associative design. Data were collected from 100 students selected through purposive sampling and who had experience purchasing fashion products through TikTok Shop. Multiple linear regression with SPSS version 29 was used to test partial and simultaneous effects at a 5% significance level. The findings showed that live streaming had a positive and significant effect on purchasing decisions. Free shipping also had a positive and significant effect on purchasing decisions and was proven to be the most dominant variable with a Standardized Beta value of 0.446. Similarly, bonus packs had a positive and significant effect on purchasing decisions. Simultaneously, the three variables had a positive and significant effect on purchasing decisions with a contribution of 83.4% (R² = 0.834). These findings imply that sellers on TikTok Shop need to optimize the quality of live streaming, maintain the free shipping program, and offer attractive bonus packs. Future studies are recommended to add other variables such as flash sales and online customer reviews with a wider population.